Relationship between anxiety and food consumption: a literature review (Research, Society and Development, 2022)
Introduction: With the evolution of humanity, food has undergone several changes to adapt to food practicality, resulting in the excessive intake of foods with a high concentration of sugars, fats and few nutrients, which can contribute to the appearance of disorders, such as the anxiety. This can be understood as a phenomenon that will harm and benefit the population depending on its situation and intensity in which it presents itself. University students are the group most affected by this disorder due to self-demand for better results, and it can end up creating a compensatory mechanism through food intake, especially industrialized foods. Objective: To analyze the relationship between eating and anxiety. Methodology: this is a literature review obtained through bibliographic surveys. Result: 10 articles were selected that point out anxiety being more prevalent among young people, especially university students, unhealthy eating was the predominant factor among the studies as a contributor to anxiety, especially those with high calorie content such as industrialized ones. Conclusion: Unhealthy eating is common among university students, which is directly related to anxiety. Further studies on the subject and interventions are needed to alleviate the problem.